2016
DOI: 10.5944/openpraxis.8.4.305
|View full text |Cite
|
Sign up to set email alerts
|

Web Strategies for the Curation and Discovery of Open Educational Resources

Abstract: For those receiving funding from the UK HEFCE-funded Open Educational Resource Programme (2009)(2010)(2011)(2012), the sustainability of project outputs was one of a number of essential goals. Our approach for the hosting and distribution of health and life science open educational resources (OER) was based on the utilisation of the WordPress.org blogging platform and search engine optimisation (SEO) techniques to curate content and widen discovery. This paper outlines the approaches taken and tools used at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In this project, like in other similar ones (Rolfe, 2016), the analytics from the repository provide evidence that teachers engage in the first stage in the OER lifecycle, 'finding'. However, the analytics data does not offer any evidence of reuse, as teachers don't make use of the 'comment' or 'like' facilities that might have provided a hint of whether the materials were being reused.…”
Section: Context Of the Studymentioning
confidence: 60%
“…In this project, like in other similar ones (Rolfe, 2016), the analytics from the repository provide evidence that teachers engage in the first stage in the OER lifecycle, 'finding'. However, the analytics data does not offer any evidence of reuse, as teachers don't make use of the 'comment' or 'like' facilities that might have provided a hint of whether the materials were being reused.…”
Section: Context Of the Studymentioning
confidence: 60%
“…Athenas and Havemann (2014) consider repositories as key to the success of the OER movement as they provide opportunities for educators to share, discover and re-use quality resources. However, Rolfe (2016) found that resources stored on external platforms received more site visits than those in institutional repositories (2016). There are very different levels of openness for Case A and B's repositories: Case A's default sharing setting is 'university only' whereas Case B's is 2010and Beggan (2010) have also highlighted these issues as barriers to engagement with OER.…”
Section: How the Libraries Support Oermentioning
confidence: 99%
“…Ferguson (2017) states that for academic libraries to continue to participate in OER conversations, they must adapt to the needs of departments, staff and students. Rolfe's (2016) arguments suggest that institutional repositories may not provide the most effective OER access point, with external websites and SEO potentially broadening exposure and access. This raises the question of whether library OER services should move away from traditional library curation strategies, such as in-house storage, and focus on other forms of support.…”
Section: Barriers Affecting the Ability Of Academic Libraries To Provmentioning
confidence: 99%
“…These projects shared OER on laboratory skills, sickle cell anaemia and blood disorders, and other life science subjects (Rolfe, 2016). Staff engaged in projects as OER creators, facilitated students as co-producers, and using OER in teaching sessions.…”
Section: Participants and Contextmentioning
confidence: 99%